The Danao languages Magindanaon, Iranun, Maranao, and Illanun - Fleischman, Eric (1981)
The three Danao1 languages of Mindanao?Magindanaon,2 Iranun, and Maranao?together with the Illanun of Sabah have long been recognized as possessing a close genetic relationship 3 (Conklin 1955; Thomas and Healey 1962; Llamzon 1974: 18-9; Leber 1975:35; Allison 1979; Walton 1979). Recent studies (Llamzon and Martin 1976; Walton 1979), moreover, have shown that the Danao languages are most closely related genetically with the Subanun group of languages and that, together with the Manobo languages, they combine to form the Meso-Mindanaon subgroup of the Southern Philippine languages (Walton 1979:78).4 To date, however, there has been no study, with the exception of Allison?s (1979) historical reconstruction of Proto-Danao,5 which has been directly concerned with the interrelationships of the Danao languages or of the dialects which form these languages. The purpose of this study is to describe the Danao languages by examining the dialects which comprise each of these languages and by delineating the interralationships between these languages in an effort to answer some of Collapse.
Includes bibliographical references (pages 73-74)
Keywords: Magindanao language; Iranun language; Maranao language